Manfaat mendengarkan lagu berbahasa Inggris dalam memperkaya kosakata untuk siswa EFL - Putri, Eka Amalia (Maliki Interdisciplinary Journal, 2024)
In the era of globalization and industrial revolution 5.0, mastery of English is very important to compete in various fields. One of the main aspects in learning English is vocabulary acquisition. However, conventional ways of enriching vocabulary, such as memorizing word lists, are often considered boring. One fun alternative is to listen to English songs. The author uses the literature study method. This study aims to find out the benefits of listening to English songs to increase vocabulary memorization for EFL students. Through auditory learning style, listening to songs can strengthen long-term memory, improve listening skills, and help pronunciation and intonation. Songs can also help students memorize vocabulary easily through the repetition of words in the lyrics. In addition, listening to songs regularly can improve phonological awareness, which is important in understanding how words are pronounced appropriately. Therefore, using songs in English learning can be a fun and effective method. Teachers should integrate songs in learning activities to improve students’ language skills naturally and efficiently.